2019
DOI: 10.1038/s41598-019-45012-6
|View full text |Cite
|
Sign up to set email alerts
|

Infiltrating CCR2+ monocytes and their progenies, fibrocytes, contribute to colon fibrosis by inhibiting collagen degradation through the production of TIMP-1

Abstract: Intestinal fibrosis is a serious complication in inflammatory bowel disease (IBD). Despite the remarkable success of recent anti-inflammatory therapies for IBD, incidence of intestinal fibrosis and need for bowel resection have not significantly changed. To clarify the contribution of haematopoietic-derived cells in intestinal fibrosis, we prepared bone marrow (BM) chimeric mice (chimeras), which were reconstituted with BM cells derived from enhanced green fluorescent protein (EGFP)-transgenic mice or CC chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 71 publications
6
39
0
Order By: Relevance
“…42 Driven by TGF-β 1 , the fibrocytes may differentiate into myofibroblasts, which are recognized as the effector cells of fibrogenesis. 11,12,15,[77][78][79] Finally, Kuroda et al 80 suggest that fibrocytes promote colon fibrosis by inhibiting collagen degradation through the production of TIMP-1.…”
Section: The Role Of Fibrocytes In Scarring and Fibrosismentioning
confidence: 99%
“…42 Driven by TGF-β 1 , the fibrocytes may differentiate into myofibroblasts, which are recognized as the effector cells of fibrogenesis. 11,12,15,[77][78][79] Finally, Kuroda et al 80 suggest that fibrocytes promote colon fibrosis by inhibiting collagen degradation through the production of TIMP-1.…”
Section: The Role Of Fibrocytes In Scarring and Fibrosismentioning
confidence: 99%
“…Therefore, the regulation of the cells is essential for reducing colon fibrosis in patients with inflammatory bowel disease (IBD). [54][55][56] The effect of restraint stress treatment on changes in colonic fibrosis was examined by Sirud Red staining and Masson's trichrome staining with the observation method of light microscope, polarization microscope and TEM, it is found that there is a clear correlation between increased interstitial collagen and increased plasma concentration of TIMP-1 with morphological and biochemical evidence of ECM accumulation. All these indicate that dysregulated matrix remodeling may be one of the reasons for inhibiting stress and HTN-induced intestinal fibrosis pathology.…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrates not only that CFP is increased in patients with acute appendicitis, but that the proportion of fibrocytes in circulating white cells may be of diagnostic value in patients presenting with suspected appendicitis. The CFP increases in response to systemic and localized inflammatory conditions 32,[40][41][42] . Circulating fibrocytes contribute to the intestinal mesenchymal cells, which comprise a spectrum of cell types that are similar in origin, function and molecular markers.…”
Section: Discussionmentioning
confidence: 99%